Trade measures for environmental protection in the World Trade Organization (WTO): Implications for developing countries - Uzma, Haroon (2014)
This study examines the extent to which rules of World Trade Organization (WTO) can serve the objectives of environmental protection through the enforcement of unilateral trade measures particularly with reference to developing countries. The potential conflicts between the substantive principles of WTO and trade-related environmental measures have resulted in serious disagreement between developed and developing countries since last three decades. Although the relationship between WTO rules and environmental measures has not been clearly established, however, the applicability of Article XX (b) and (g) of GATT provides a connection between trade and environmental objectives. This study adopts interpretative and analytical techniques for data analysis. The purpose of this study was to undertake detailed analyses of WTO’s judicial and legislative approaches with regard to permissibility and legality of environmentally motivated unilateral trade measures. Judicial approach of WTO explores the development of environmental jurisprudence established by the Panels and Appellate Body decisions. The Multilateral Environmental Agreements (MEAs) have been recommended by the WTO as a better solution to transboundary environmental problems. This study also focuses on the legislative approach of WTO, comprising of work programme of Committee on Trade and Environment (CTE) regarding WTO- MEA relationship. This study proposes a voluntary consultation procedure for clarification of MEA-related trade measures based upon the principles originally presented by New Zealand during Doha negotiations. The study concludes by emphasizing upon the need for more integrated and innovative positive measures for developing countries to offset the negative implications of unilateral trade measures